Anatomy of the canine appendicular skeleton and major limb malformations (Research, Society and Development, 2024)
The limbs of dogs, divided into thoracic and pelvic, are essential for support, locomotion, and impact absorption, each composed of specific bones such as the scapula, humerus, radius, ulna, femur, tibia, and fibula. Appendicular bone malformations in dogs are a group of conditions that affect the normal development of the skeleton, potentially leading to a range of health and well-being issues for these animals. Based on this, this work aims to present the anatomy of the canine appendicular skeleton and compare it with the anatomical changes found in the main malformations, as well as their clinical implications, through a literature review. These alterations can be congenital, meaning present from birth, or acquired throughout the animal's life due to environmental, nutritional, or traumatic factors. Among the most common bone malformations in the limbs of dogs are hip dysplasia, elbow dysplasia, and patellar luxation. Hip dysplasia is characterized by a malformation of the hip joint, resulting in instability and pain, which can lead to secondary osteoarthritis. Elbow dysplasia involves changes in the humeroradioulnar joints, causing lameness and discomfort. Patellar luxation, on the other hand, is a condition where the patella dislocates from the trochlear groove of the femur, causing pain and lameness. Therefore, early identification of malformations is crucial for proper management and the implementation of therapeutic interventions that can improve function and quality of life for the patients.